2016
DOI: 10.1080/10715762.2016.1194519
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of phagocytic activity of ARPE-19 cells by free radical mediated oxidative stress

Abstract: Oxidative stress is a main factor responsible for key changes leading to the onset of age-related macular degeneration (ARMD) that occur in the retinal pigment epithelium (RPE), which is involved in phagocytosis of photoreceptor outer segments (POS). In this study, hydrogen peroxide (H2O2), H2O2 and iron ions (Fe) or rose Bengal (RB) in the presence of NADH and Fe were used to model free radical mediated oxidative stress to test if free radicals and singlet oxygen have different efficiency to inhibit phagocyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…This results in a vicious circle ultimately leading to apoptosis. The sustained high concentration of intracellular Ca 2+ , followed by activation of calpains, which critically mediates the subsequent ER-mitochondrial cross-talk [ 49 , 50 , 51 , 52 , 53 ]. Recent studies have shown that Ca 2+ is associated with the formation of the autophagosome [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…This results in a vicious circle ultimately leading to apoptosis. The sustained high concentration of intracellular Ca 2+ , followed by activation of calpains, which critically mediates the subsequent ER-mitochondrial cross-talk [ 49 , 50 , 51 , 52 , 53 ]. Recent studies have shown that Ca 2+ is associated with the formation of the autophagosome [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, while Lf isolated from human donors of 18–29 years old decreased phagocytosis of POS by 10 and 30% when ARPE‐19 cells when irradiated with blue light for 2 and 3 h, respectively, Lf from donors of 50–59 years old, inhibited the phagocytosis in that case by 20 and 60% . The observed photoinhibition of the phagocytic activity of ARPE‐19 cells, most likely results from sub‐lethal damage of the cell phagocytic apparatus, induced by photodynamic action mediated by an appropriate photosensitizer or by reactive oxygen species accompanying oxidative stress …”
Section: Resultsmentioning
confidence: 94%
“…To quantify the cytotoxic effect of photic stress in ARPE‐19 cells, MTT assay for mitochondrial redox function was used 24 h after the cell irradiation . According to the protocol, MTT solution (final concentration 0.5 mg mL −1 ) in MEM with 10% FBS was added to light treated cultures incubated with HBSS alone (control) or fed with LUV.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, longterm responses to phagocytosis or oxidative stress share common features in human RPE (44). However, an inhibitory effect of reactive oxygen intermediates on phagocytosis has also been observed (45). Considering the dynamic nature of phosphorylation events, we can speculate that the role of particular phosphorylation cascades changes as the phagocytic process progresses, possibly as different stimuli reach the phagocytosing cell.…”
Section: Rpe-j Cellsmentioning
confidence: 90%